Fermented Catfish Oil on Cognitive Function - Ngadiarti, Iskari; Kusharto, Clara M.; Briawan, Dodik; Marliyati, Sri Anna; Sajuthi, Dondin (Pakistan Journal of Nutrition, 2013)
The relationship between fatty acid composition with levels of amyloid beta and tau proteins in the cerebrospinal fluid is not widely known. The aim of this study was to assess the influence of catfish oil (CFO) and fermented catfish oil (FCFO) on cognitive functions (biology markers) aged female cynomolgus monkey (Cynomolgus fascicularis). Twelve aged female Cynomolgus were divided into 4 groups, each were fed with atherogenic iso calory with 0.2% cholesterol and 30% E (12% w/w), 3% from soybean oil, 9% from different fat sources, beeftallow (BFT), catfish oil (CFO), fermented cat fish oil (FCFO) and soybean oil (SBO). Cerebrospinal fluid was taken through suboccipital then kept at 20°C. Cognitive biology markers which were analyzed by using Tau and Aβ42ELISA kits. Changes in level of amyloid beta, tau protein and ratio of tau protein and amyloid beta were not statistically significant in the cynomolgus group four that were fed with BFT, FCFO, CFO and SBO, despite a trend toward increased levels of amyloid beta and decreased level of the tau protein / amyloid beta ratio were found in the group given with FCFO and CFO. In summary, FCFO and CFO intake capable to improve the cognitive function based on biological biomarkers.